Experimental investigation of the laminar flow and heat transfer performance of a harmonica tube with or without mini-fins. (5th January 2020) - Wang, Yiwei; Dong, Ti; Cao, Wenjiong; Peng, Peng; Jiang, Fangming
Highlights: Experimental study on heat transfer performance of harmonica tubes with mini-fins. The harmonica tube with mini-fins can have much improved heat transfer performance. The fluid temperature has influence on the tube's heat transfer performance. The mini-finned channel number and size show influence on the tube's performance. Abstract: Thermal and flow performance was evaluated experimentally for different geometric shapes of a harmonica tube with or without mini-fins heat sink. Four different arrangements for the harmonica tube with smooth channels and channels with mini-fins were investigated under laminar forced convection with water as the cooling fluid. The pressure drop, friction factor and volumetric heat transfer coefficient were determined for Reynolds number ranging from 250 to 2300, and the four harmonica tube arrangements were compared. The results show that the transition from the laminar to turbulent flow regimes shifts to a smaller Reynolds number due to the presence of the mini-fins as compared to the smooth channels. An increase of the inlet fluid temperature leads to a reduction of the heat transfer performance and also flow resistance. Due mainly to the augmented heat transfer surface, the performance evaluation criterion value of the harmonica tube with mini-fins is always higher than 1 in the researched Reynolds number range and it can be as high as about 1.7 when the fluid flow is in the laminar to turbulent transition regime. Moreover, it is found that lowering the height of mini-channels, or for a given mini-channel geometry, increasing the number of mini-channels can improve the overall heat transfer performance of the harmonica tube with mini-fins.